From Doubt to Drive: Students’ Lived Narratives of Motivation, Self-Regulated Learning, and Social Support as Pathways to Academic Success in Indonesian Senior High Schools - M. Yusron Maulana El Yunusi; Didit Darmawan; Vugar Abdullayev (International Journal of Educational Narratives, 2026)
Background. Academic achievement in Indonesian senior high schools is increasingly challenged by heightened competition, uneven access to digital learning resources, and variability in students’ psychological preparedness. Despite widespread implementation of digital tools and social support programs, there remains uncertainty regarding which factors most strongly influence student success in this rapidly changing educational landscape. Identifying the key predictors of academic performance is therefore critical to inform targeted interventions that can address both equity and effectiveness in student learning outcomes. Purpose. This study aims to examine the effect of learning motivation, academic self-efficacy, digital skills, self-regulated learning strategies, and academic social support on academic performance of public senior high school students in Surabaya. Method. The research method used was quantitative with an explanatory survey approach. The sample consisted of 387 public senior high school students in Surabaya selected using purposive sampling technique. Data collection was conducted through an online Likert-scale questionnaire distributed via Guidance and Counseling teachers for three days. The research instrument had been tested for validity and reliability with Cronbach’s Alpha values for each variable above 0.82. Data analysis technique used multiple linear regression with SPSS version 26. Results. Simultaneously, all five independent variables had a significant effect on academic performance, explaining 38.9% of the variance (R² = 0.389, p < 0.001). Partially, learning motivation (? = 0.27, p = 0.002), academic self-efficacy (? = 0.35, p < 0.001), and self-regulated learning strategies (? = 0.23, p = 0.005) had positive and significant effects on academic performance. Digital skills (? = 0.08, p = 0.124) and academic social support (? = 0.06, p = 0.187) did not significantly affect performance. Academic self-efficacy was the most dominant contributing factor. Conclusion. The findings indicate that students’ internal psychological factors, particularly academic self-efficacy and self-regulated learning strategies, are more strongly associated with academic performance than digital competence and social support. The study recommends interventions aimed at enhancing these internal factors to improve student academic outcomes.